ANALISIS PENGEMBANGAN WISATA ALAM AIR TERJUN WIDURI SEBAGAI KAWASAN EKOLOGI PARIWISATA - Lailiyatun Nasikhah; Achmad Ali Fikri (Universitas Pakuan, 2021)
Widuri Waterfall has its own uniqueness compared to other tourist attractions in Grobogan. The natural nature of the Widuri Waterfall is the main attraction for visitors. This study aims to explore how the development of ecotourism in the Widuri waterfall area has applied the principles of ecotourism or not. This research is included in the field research, with a qualitative approach and descriptive analysis. Data collection techniques in the form of interviews, observation and literature study. Based on the research that has been carried out, it is found that in tourism development every year holding environmental conservation activities, every tree around the tourism is given a name and its benefits, then tourism development has also involved the role of the local community. It can be concluded that the development of Widuri waterfall tourism has met the requirements of the principles of eco-friendly tourism development, namely the existence of the principle of conservation, the principle of education, the principle of tourism, the principle of economics and the principle of community participation. Researchers suggest to managers to continue to evaluate continuously in the development of ecotourism Widuri waterfall so as not to disturb and damage the function of the natural environment around the Widuri waterfall area. With this research, it is hoped that tourism managers will continue to pay attention to the principles of tourism development based on the principles of ecological development. Keywords: Development, Ecotourism, Waterfall